Comparative Learning Study of Third Grade Supriyadi Elementary School in Indonesia and Feu Roosevelt Elementary School in Philippines - Hastutik, Indah Puji; Priyanto, Wawan; Rofian, Rofian (Universitas Pendidikan Ganesha, 2020)
The low quality of education in Indonesia is still low, so the analysis is needed to compare it with education carried out by other countries. This study aimed to analyze a conclusion by comparing two different objects, namely comparing the existing learning system in one of the primary schools in Indonesia and the Philippines. The type of research used is a descriptive approach. Supriyadi Elementary School's third-grade students in Indonesia and third grade Roosevelt Elementary School in Philippines studied the research subjects studied. The data collection methods used were observation, interviews, and documentation. The methods and data analysis techniques used are qualitative statistical analysis. This study indicates that the learning process has strategies that can make learning very meaningful, learning tools and learning media to measure learner success and learning evaluation, consisting of aspects of knowledge, social attitudes, and skills. This research implies that knowing the analysis of differences in learning between Indonesia and the Philippines can add insight into teachers' differences in Philippines' learning.